A Cadaveric Study Investigating the Mechanism of Action of Erector Spinae Blockade. Issue 6 (August 2018) - Ivanusic, Jason; Konishi, Yasutaka; Barrington, Michael J.
Abstract : Background and Objectives: Erector spinae block is an ultrasound-guided interfascial plane block first described in 2016. The objectives of this cadaveric dye injection and dissection study were to simulate an erector spinae block to determine if dye would spread anteriorly to the involve origins of the ventral and dorsal branches of the spinal nerves. Methods: In 10 unembalmed human cadavers, 20 mL of 0.25% methylene blue dye was injected bilaterally into the plane between the fifth thoracic transverse process and erector spinae muscle. An in-plane ultrasound-guided technique with the transducer orientated longitudinally was used. During dissection, superficial and deep muscles were identified, and extent of dye spread was documented in cephalocaudal and lateral directions. The ventral and dorsal rami of spinal nerves and dorsal root ganglion at each level were examined to determine if they were stained by dye. Results: There was extensive cephalocaudad and lateral spread of dye deep and superficial to the erector spinae muscles. Except for 1 injection (from 20), the ventral rami were not stained by the dye. In only 2 injections did the dye track posteriorly through the costotransverse foramen to the dorsal root ganglion. In all other cases, the dorsal root ganglia were not involved in the dye injection. The dye stained the dorsal rami posterior to the costotransverse foramen. Conclusions: There was no spread of dye anteriorly to the paravertebral space to involve origins of the ventral and dorsal branches of the thoracic spinal nerves. Dorsal ramus involvement was posterior to the costotransverse foramen.